Respostas

A melhor resposta!
2014-05-29T19:18:46-03:00
Simplifique as seguintes expressões:

a-)x² - 5x + 6 / x² - 9

  x² - 5x + 6     (x - 3)(x - 2)       (x - 3)(x - 2)  : (x - 3)       (x + 2)
--------------- = ---------------- = ----------------               =  --------   ==  x+2/x+3
    x² - 9          (x - 3)( x+ 3)      (x - 3)(x + 3)   : (x - 3)      (x + 3) 

b-)3x^4 - 10x² / x^5 - x²

  3x⁴ - 10x²        x²( 3x² - 10)       x²(3x² - 10) : x²        3x² - 10
-------------- =  ----------------  =   --------------         =  ---------- =  =  3x² - 10/x³-1
   x⁵ - x²             x²(x³ - 1)              x²(x³ - 1)   : x²          x³ - 1

c-)x² - 9 / x - 3
 
   x² - 9      (x - 3)(x + 3)        (x - 3)(x + 3)  :(x - 3)       x + 3
---------- = ----------------- =   ----------------              =   ------ ==  x + 3
   x - 3             x - 3                   x - 3          :(x - 3)          

2 4 2